Not Baseline Atrial Fibrillation but New-Onset Atrial Fibrillation and the Loss of Left Atrial Function Are Essential for Predicting Poor Outcomes in Non-ischemic Cardiomyopathy - Okune, Mana; Yasuda, Masakazu; Soejima, Naoko; Kakehi, Kazuyoshi; Kawamura, Takayuki; Kurita, Takashi; Nakazawa, Gaku; Iwanaga, Yoshitaka (Frontiers in Cardiovascular Medicine, 2021)
Aims: The clinical impact of the type of atrial fibrillation (AF) has not been completely elucidated in non-ischemic cardiomyopathy (NICM). Although the structure and function of the left atrium (LA) provide prognostic information in patients with heart failure, the relationship of the AF type with LA structure and function in NICM is unclear. Methods: Consecutive patients with NICM who underwent cardiac magnetic resonance were evaluated and followed. Multivariable Cox regression models were used to estimate hazard ratios (HRs) for major adverse cardiovascular events (MACE) related to the AF type, such as paroxysmal AF, chronic AF, and new-onset AF (NOAF). Results: Among 625 patients with NICM (mean age, 64.4 ± 14.2 years; women, 39.7%), 133 had a history of AF at baseline; of these, 60 had paroxysmal AF. Each baseline AF type was associated with higher LA volume and lower LA emptying fraction but not with an increased incidence of MACE (p = 0.245). New-onset AF developed in 5.9% of patients with sinus rhythm over a median follow-up period of 609 days, and maximum LA volume was a strong and independent predictor [p < 0.001, area under the ROC curve (AUC): 0.795]. Maximum LA volume was superior to LA emptying fraction and B-type natriuretic peptide (AUC: 0.683 and 0.680, respectively). The use of β-blocker and the age of the patient were associated with the incidence of NOAF (HR: 0.37, 95% CI: 0.16–0.84 and HR: 1.05, 95% CI: 1.01–1.09, respectively). Kaplan–Meier analysis showed that patients with NOAF had a higher incidence of MACE than those with sinus rhythm or baseline AF (p = 0.002). NOAF and LA emptying fraction were independent predictors of MACE (HR: 2.28, 95% CI: 1.20–3.97 and HR: 0.98, 95% CI: 0.96–0.99, respectively) after adjusting for age, sex, body mass index, and diagnosis. Conclusions: Paroxysmal and chronic AF in patients with NICM were not associated with an increased incidence of MACE despite their association with LA volume and function. NOAF was independently associated with poor prognosis. Higher maximum LA volume predicted the onset and lower LA emptying fraction was independently associated with poor prognosis.